ФОРМУВАННЯ КОНКУРЕНТОСПРОМОЖНОГО ПОТЕНЦІАЛУ РОБОЧОЇ СИЛИ В УКРАЇНІ - Дмитренко, А. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The problems of forming of competitive human potential are considered. Basic directions of forming of high-quality side of labour potential as terms of achievement of competitive level of labour force are defined, the estimation of marketability different constituents of this process, which determine reality of general change of situation, is given.